Picrotoxin but not bicuculline partially abolishes the cardio-inhibitory responses induced by visual stimulation in the crab Neohelice granulata - Yang, M. (2012)
Conspicuous and sustained heart arrests, revealed as an increase in the magnitude of cardiac interbeat intervals, are elicited in the crab Neohelice granulata upon the presentation of a visual danger stimulus (VDS). Aiming to study the regulation of cardio-inhibitory responses (CIR) in vivo, we investigated whether GABA mediates the extrinsic regulation of the cardiac activity. We examined the possibility of abolishing CIR by injecting the GABAergic antagonists picrotoxin and bicuculline, right before sensory stimulation. Picrotoxin partially abolished the reversible cardiac arrests induced by VDS, whereas bicuculline showed no effects. These results suggest that the rapid responses of the cardiac system of the crab Neohelice to environmental disturbances, reminiscent of an autonomic-like regulation associated with fear, flight or fight, may be extrinsically regulated by the GABAergic system.